Requirements for practicing the auditing profession in the lights of the international auditing standards “an analytical study - ziadi, sami; saidi, yahia (Journal of Research in Finance and Accounting, 2021)
This study aims to highlight the importance of the requirements needed for practicing the auditing profession set forth by international auditing standards. These requirements represent the basis for building the auditor’s professional character, and help him maintain his independence and enable him to perform his work with enough care. The study reached a number of results, the most important of which is that the international auditing standards have covered most of the auditing general standards requirements, although they did not determine special standards for that. rather, they dealt with these aspects through a set of rules stipulated in more than one standard.